Selection of optimal technique for greywater pretreatment - Amer Hasan Taher; Ahmed Mancy Mosa; Lubna Abdulrahman (Heritage and Sustainable Development)
Greywater can be reused after treatment. Several techniques for treating greywater can be adopted. However, the selection of the optimal technique is a difficult action. Therefore, this study adopted an experimental approach to compare two different techniques to determine the optimal one. Two systems were designed and constructed to study the optimal technique for greywater pretreatment. The first system consists of a 5000L anaerobic fiberglass tank of 2.5m depth whereas the other system consists of 5 separated cylindrical tanks; each tank of 1000L fiberglass. The pH, biological oxygen demand (BOD5), total suspended solids (TSS), Total N, Total P, chemical oxygen demand (COD), total organic Carbon (TOC), SO4, Alkaline, Na+1, Ca+2, K+1, and water temperature for raw greywater and effluent from each tank were continuously measured for ten months. According to performance data, ineffective anaerobic bacteria weaken wastewater in septic tanks by roughly 30–40% while extremely effective aerobic bacteria do the same in protonated tanks by more than 93%. Compared to anaerobic bacteria, aerobic bacteria enhance the quality of greywater that exits a septic tank. The present study exposed the nitrification of waste through aerobic treatment of greywater using ozone and air (1:1 volume %) to reduce odor, COD, TSS, and BOD5 and remove nitrogen.